2011
DOI: 10.17221/292/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Application of wheat B-starch in biodegradable plastic materials

Abstract: AbstractŠárka E., Kruliš Z., Kotek J., Růžek L., Korbářová A., Bubník Z., Růžková M. (2011): Application of wheat B-starch in biodegradable plastic materials. Czech J. Food Sci., 29: 232-242.Food application of wheat B-starch comprising small starch granules as a result of lower quality is problematic. Accordingly, B-starch or acetylated starch prepared from it, with the degree of substitution (DS) of 1.5-2.3, was used in biodegradable films after blending with poly-(ε-caprolactone) (PCL). The following mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Commercial acetylated potato starch (PS) “Solvarin OBV” of DS 0.04 and dry substance 82.5% was provided by the Škrobárny Pelhřimov starch company (Czech Republic). Acetylated wheat B‐starch of DS 1.4 was prepared in the laboratory as described by Šárka et al 19 (N‐content 0.23%, 90.4% of acetylated starch in dry substance). The mean average diameter of milled aggregates was 8.7 µm, as determined by image analysis and the dry substance was 95.8%.…”
Section: Methodsmentioning
confidence: 99%
“…Commercial acetylated potato starch (PS) “Solvarin OBV” of DS 0.04 and dry substance 82.5% was provided by the Škrobárny Pelhřimov starch company (Czech Republic). Acetylated wheat B‐starch of DS 1.4 was prepared in the laboratory as described by Šárka et al 19 (N‐content 0.23%, 90.4% of acetylated starch in dry substance). The mean average diameter of milled aggregates was 8.7 µm, as determined by image analysis and the dry substance was 95.8%.…”
Section: Methodsmentioning
confidence: 99%
“…Campos et al observed increases in tensile strength, elongation at break, and elasticity modulus of SPCL composites after UV irradiation. Sarka et al reported an increase in elastic modulus and strength of PCL composites with acetylated starch in comparison with those of composites obtained from native starch. According to Yavuz and Babaç, crosslinked starch composited with PCL shows improved tensile strength and elongation at break.…”
Section: Properties Of Spcl Compositementioning
confidence: 99%
“…Starch-based materials are attractive due to their biodegradability and wide range of applications, such as packaging, coating, agriculture, medicine, pharmacy, or even optoelectronics (Sarka et al, 2011(Sarka et al, , 2012Saiah et al, 2012;Xie et al, 2013;Ghavimi et al, 2015;Oleyaei et al, 2016a;Campos-Requena et al, 2017;Dufresne and Castano, 2017;Javanbakht and Namazi, 2017;Kuswandi, 2017;Liu G. et al, 2017;Liu S. et al, 2017;Sarka and Dvoracek, 2017, Ilyas et al, 2018, Ilyas et al, 2019. However, the melting temperature of native starch is higher than its degradation temperature.…”
Section: Introductionmentioning
confidence: 99%